2013
DOI: 10.1177/1059601113492421
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting at the Team and Individual Level

Abstract: Previous research suggests that employee job crafting is positively related to job performance through employee work engagement. The present study expands this individual-level perspective to the team level by hypothesizing that team job crafting relates positively to team performance through team work engagement. In addition, on the basis of social psychological theories about norms, modeling, and emotional contagion in groups, we hypothesize that team job crafting relates to individual performance through (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(215 citation statements)
references
References 77 publications
8
197
1
9
Order By: Relevance
“…Although the crafted job should be better aligned to the needs of employees with a limited FTP, which is expected to lead to higher levels of work engagement and better job performance, earlier studies on job crafting found that decreasing hindering job demands is not or even negatively associated with work engagement and job performance (Tims et al, 2013a;Tims, Bakker, & Derks, 2015;Tims, Bakker, Derks, & Van Rhenen, 2013b). For example, decreasing hindering job demands was negatively related to vigour, the energy aspect of work engagement (Tims et al, 2013b), implying that decreasing hindering job demands costs energy and will therefore have a negative influence on work engagement and job performance. In addition, the crafted job might be less psychologically stimulating, subsequently leading to boredom and thus decreased levels of work engagement (Petrou et al, 2012).…”
Section: The Associations Between Ftp and Job Craftingmentioning
confidence: 99%
“…Although the crafted job should be better aligned to the needs of employees with a limited FTP, which is expected to lead to higher levels of work engagement and better job performance, earlier studies on job crafting found that decreasing hindering job demands is not or even negatively associated with work engagement and job performance (Tims et al, 2013a;Tims, Bakker, & Derks, 2015;Tims, Bakker, Derks, & Van Rhenen, 2013b). For example, decreasing hindering job demands was negatively related to vigour, the energy aspect of work engagement (Tims et al, 2013b), implying that decreasing hindering job demands costs energy and will therefore have a negative influence on work engagement and job performance. In addition, the crafted job might be less psychologically stimulating, subsequently leading to boredom and thus decreased levels of work engagement (Petrou et al, 2012).…”
Section: The Associations Between Ftp and Job Craftingmentioning
confidence: 99%
“…Posteriormente, se corroboraram evidências de que o job crafting além de estar positivamente relacionado ao desempenho individual via engajamento no trabalho, pôde também ser utilizado simultaneamente ao nível da equipe para melhorar o desempenho no trabalho (Tims, Bakker, Derks, & Rhenen, 2013). Por outro lado, os efeitos das ações de job crafting, especificamente aquelas que buscaram reduzir as demandas de trabalho consideradas obstáculos para o indivíduo, estiveram positivamente relacionadas à sobrecarga e ao conflito entre colegas, e por sua vez ao burnout dos colegas de trabalho (Tims, Bakker & Derks, 2015).…”
Section: Instrumentounclassified
“…In regard to the relationship between job crafting and work engagement, past research has shown a significant relationship between the two variables. In a longitudinal study based on Tims and Bakker's (2010) proposition, Tims, Bakker, Derks, and Van Rhenen, (2013b) found that employees impact work engagement, job satisfaction, and burnout by crafting structural (i.e., equivalent to task crafting) or social job resources (i.e., equivalent to relational crafting) via increases in the respected variables. In addition, the amount of challenging job demands partially mediated the relationship between crafting challenging job demands and work engagement and burnout.…”
Section: Job Crafting and Individual Attitudes And Behaviorsmentioning
confidence: 99%
“…In addition, the amount of challenging job demands partially mediated the relationship between crafting challenging job demands and work engagement and burnout. In a different study, Tims et al (2013b) examined 525 individuals in a large occupational health services company and investigated job crafting at the individual and team levels. They observed that job crafting influenced both individual work engagement and team work engagement.…”
Section: Job Crafting and Individual Attitudes And Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation